PENINGKATAN KESUBURAN TANAH DAN HASIL PADI SAWAH MELALUI APLIKASI PUPUK ORGANIK - Itang Ahmad Mahbub; Gindo Tampubolon; Mukhsin Mukhsin; Yulfita Farni (Jurnal Tanah dan Sumberdaya Lahan, 2023)
The yield of irrigated paddy rice in Sri Agung Village has decreased. In the last four years, the increase in the addition of input units (fertilizers) has not been followed by an increase in economic yields. This study aims to analyze the effect of organic fertilizers on soil fertility, such as pH, total N, organic C, available P and available K. The research was conducted in the rice fields of Sri Agung Village. Batang Asam area, West Tanjung Jabung Regency - Jambi. The research was conducted from April to September 2020. The study used a randomized block design with six treatments and five replications. The treatments tried were: Recommended Fertilizer (R), five types of organic fertilizer with a dose of 10 t ha-1 each, namely, Petroganik+R ( P1), Compost Solid Decanter + R (P2), Chicken Manure + R (P3 ), Cow Manure +R (P4) and Industrial Waste Compost + R (P5). The results showed that organic fertilizers significantly increased available K content of paddy soil but they did not significantly increase soil pH, total N, organic C and available P. The highest yield of dry milled grain (7.52 t ha-1) was obtained at +R (P1) Petroganic treatment.